1995
DOI: 10.1007/bf01543106
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Cowan I-induced human immunoglobulin responses: Preferential IgM rheumatoid factor production and VH3 mRNA expression by protein A-binding B cells

Abstract: Protein A (PA), a cell wall component of SAC, activates human B cells by cross-linking the Fabs of membrane immunoglobulins. Recent data indicate that PA binds only to Fabs that use VH3 heavy chains, and thus it has been designated as a B-cell superantigen. We previously reported that Staphylococcus aureus Cowan I (SAC)-induced IgM rheumatoid factor (RF) by human PBMC was mediated by PA. Therefore, we sought to determine if SAC-induced IgMRF production was confined to PA-binding B cells and if these B cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Other staphylococcal superantigens, however, favor usage of genes from the V H 3 family (27, 28). Kozlowski et al reported that IgM transcripts produced in response to S. aureus protein A are enriched for V H 3 H chains (29).…”
Section: Discussionmentioning
confidence: 99%
“…Other staphylococcal superantigens, however, favor usage of genes from the V H 3 family (27, 28). Kozlowski et al reported that IgM transcripts produced in response to S. aureus protein A are enriched for V H 3 H chains (29).…”
Section: Discussionmentioning
confidence: 99%
“…This correlation was later extended in studies of IgG and IgA Abs [30,31]. The restricted association with vH3 gene usage has now been confirmed by several other groups [16,17,, and there has not been a single reported example in which a non-V~3 Ab displayed comparable binding activity (see below).…”
Section: Specificity and Affinity Of Ab Binding To Spamentioning
confidence: 56%
“…Hence, SPA binding is thought to occur outside of the classical antigen binding site and, thus, is considered a B-cell superantigen [30]. In support of this classification, SPA has been shown not only to preferentially bind to B cells expressing VH, encoded antibodies, SPA also delivers activation signals to stimulate the differentiation of these B cells and immunoglobulin production [19,23].…”
Section: Vha Encoded Antibodiesmentioning
confidence: 97%
“…aureus Cowan I has been shown to stimulate IgM rheumatoid factor production by peripheral blood mononuclear cells of healthy people [55]. IgM R F production was limited to a subset of B cells which bound SPA and was enriched for expression of VHI encoded heavy chains [23]. Superantigens, therefore, have the potential of influencing the B cell repertoire, forming immune complexes which can activate, complement and induce the production of autoantibodies.…”
Section: Figure 7 Ribbon Drawing Of the Vh And Vl Domains Of The V H mentioning
confidence: 98%
See 1 more Smart Citation